2011
DOI: 10.4314/ejhs.v21i1.69042
|View full text |Cite
|
Sign up to set email alerts
|

Khat Chewing and Mental Distress: A Community Based Study, in Jimma City, Southwestern Ethiopia

Abstract: BackgroundKhat (Catha edulis) contains a psychoactive substance, cathinone, which produces central nervous system stimulation analogous to amphetamine. It is believed that khat chewing has a negative impact on the physical and mental health of individuals as well as the socioeconomic condition of the family and the society at large. There is lack of community based studies regarding the link between khat use and poor mental health. The objective of this study was to evaluate the association between khat use an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
70
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 12 publications
21
70
8
Order By: Relevance
“…This finding is supported by a community based study conducted on Khat Chewing and mental distress in Jimma City, South Western Ethiopia. 18 Related study which was conducted among high school students in Dire Dawa 19 confirmed that Khat chewing is strongly associated being Muslim.…”
Section: Discussionmentioning
confidence: 94%
“…This finding is supported by a community based study conducted on Khat Chewing and mental distress in Jimma City, South Western Ethiopia. 18 Related study which was conducted among high school students in Dire Dawa 19 confirmed that Khat chewing is strongly associated being Muslim.…”
Section: Discussionmentioning
confidence: 94%
“…For instance university based prevalence studies conducted in Ethiopia reported khat use prevalence ranging from 13.4% to 41% for lifetime, 7% to 20.3% for past 12 months, and 6.3% to 33.1% current or past 30 days 32 . Much bigger prevalence reports noticed in Ethiopia are from one school survey report and other community based surveys 7,34 .…”
Section: Discussionmentioning
confidence: 99%
“…The growing research evidence shows that khat is a risk factor for different cardio-vascular disorders such as hypertension, ischemic heart diseases, and stroke 3,4 . Khat is also a risk factor for poor oral health 5 , psychosis 6 , mental distress 7 , anemia 8 , poor quality of life 9 , disturbed sleep pattern [10][11][12] , and duodenal ulcer 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Khat is chewed daily by a high proportion of adult population for its Central Nervous System stimulant effect (Hussein, 2009). Furthermore, it is widely masticated among youth Ethiopians, especially high school, college and university students (Damena et al, 2011). Its effects on the chewers include increased levels of energy, increased self-esteem, euphoria, increased libido, excitement, and increased proclivity for social interaction (Deressa & Azazh, 2011;Oshodi et al, 2010).…”
mentioning
confidence: 99%